Upregulated miR-206 Aggravates Deep Vein Thrombosis by Regulating GJA1-Mediated Autophagy of Endothelial Progenitor Cells - Yan Li; Jingping Ge; Yuanyuan Yin; Ruowen Yang; Jie Kong; Jianping Gu (Cardiovascular Therapeutics)
Background. Deep vein thrombosis (DVT) is the third most prevalent vascular disease worldwide. MicroRNAs (miRNAs) play regulatory roles in functions of endothelial progenitor cells (EPCs), which is becoming a promising therapeutic choice for thrombus resolution. Nevertheless, the role of miR-206 in EPCs is unclear. Methods. EPCs were isolated from the peripheral blood of patients with DVT. In DVT mouse models, DVT was induced by stenosis of the inferior vena cava (IVC). The levels of miR-206 and gap junction protein alpha 1 (GJA1) in EPCs and vascular tissues of DVT mice were detected by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The proliferation, migration, apoptosis, and angiogenesis were tested by cell counting kit-8 (CCK-8) assay, Transwell assay, flow cytometry analysis, and in vitro tube formation assay. The levels of autophagy-related proteins as well as the level of GJA1 in EPCs and vascular tissues were evaluated by western blotting. DVT formation in vivo was observed through hematoxylin-eosin (HE) staining. The expression of thrombus resolution markers, CD34 molecule (CD34) and matrix metallopeptidase 2 (MMP2), in the thrombi was measured by immunofluorescence staining. Results. miR-206 overexpression inhibited proliferation, migration, and angiogenesis and promoted apoptosis of EPCs, while miR-206 knockdown exerted an opposite effect on EPC phenotypes. Downregulation of GJA1, the target of miR-206, abolished the influence of miR-206 on EPC phenotypes. Furthermore, silencing of miR-206 suppressed the autophagy of EPCs via upregulating GJA1. miR-206 knockdown repressed thrombus formation, enhanced the homing ability of EPCs to the thrombosis site, and facilitated thrombus resolution in DVT mouse models. Additionally, miR-206 was upregulated while GJA1 was downregulated in vascular tissues of DVT mice. miR-206 knockdown elevated GJA1 expression in vascular tissues of DVT mice. The expression of miR-206 was negatively correlated with that of GJA1 in DVT mice. Conclusion. miR-206 knockdown upregulates GJA1 to inhibit autophagy of EPCs and then promote EPC proliferation, migration, and angiogenesis, thereby enhancing EPC homing to thrombi and facilitating thrombus resolution.